Ethical action in education research from the historical and dialectical materialism perspective (Práxis Educativa, 2023)
This paper aims to present a debate on ethics in education research from the assumption that the area of Human and Social Sciences requires its own ethical guidelines and norms, surpassing the deontological model that transposes the parameters of the medical area to various research fields. The theoretical framework is the historical and dialectical materialism from the understanding that consciousness, ethical values, knowledge, and science are related to historical, economic, political, and social determinations. In this sense, the results of this investigation support the argument that it is fundamental to think about the ethical dimension in the research process and its relationship with political and epistemological issues, as criticism and overcoming abstract principles and bureaucratic procedures present in ethics protocols in education research.Keywords: Education research. Ethical foundations. Historical and dialectical materialism.